The Significance of Sovereignty in the Context of the Modern State in a Philosophical Dimension - Yunus, Nur Rohim (BULETIN ADALAH, 2024)
This essay discusses the significance of sovereignty in the context of the modern state, highlighting the transformation of the concept of sovereignty and the development of globalisation, technology, and international interdependence. Initially, sovereignty was understood as the absolute power of a state to regulate its domestic affairs. However, sovereignty must be adjusted to international norms and human rights in the global era. Globalisation and digital threats require states to balance domestic interests and global obligations. This essay also raises the dilemma of international intervention and the role of sovereignty in facing these challenges. Therefore, a more flexible, inclusive, and participatory sovereignty reinterpretation is needed, considering the state's responsibilities to its citizens and international cooperation. With this approach, state sovereignty can remain relevant and effective in responding to the challenges of the times, such as globalisation and climate change, while maintaining identity, security, and social welfare.